2015
DOI: 10.1080/10503307.2015.1049671
|View full text |Cite
|
Sign up to set email alerts
|

Therapist facilitative interpersonal skills and training status: A randomized clinical trial on alliance and outcome

Abstract: Results were consistent with the hypothesis that therapists' common relational skills are independent contributors to therapeutic alliance and outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
117
1
16

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(147 citation statements)
references
References 37 publications
11
117
1
16
Order By: Relevance
“…In addition, nonspecific elements—sometimes referred to as common factors (Barth et al 2011, Webb et al 2010)—were related to treatment effectiveness. These results are consistent with recent findings that showed among therapists in training, nonspecific skills (e.g., collaboration, empathy, and warmth) are independent contributors to patients’ outcomes (Anderson et al 2015), in particular for brief treatments (Anderson et al 2016). The competencies that providers need to deliver these nonspecific elements must be emphasized as a foundation for delivering psychological treatment.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, nonspecific elements—sometimes referred to as common factors (Barth et al 2011, Webb et al 2010)—were related to treatment effectiveness. These results are consistent with recent findings that showed among therapists in training, nonspecific skills (e.g., collaboration, empathy, and warmth) are independent contributors to patients’ outcomes (Anderson et al 2015), in particular for brief treatments (Anderson et al 2016). The competencies that providers need to deliver these nonspecific elements must be emphasized as a foundation for delivering psychological treatment.…”
Section: Discussionsupporting
confidence: 93%
“…This picture of little association between FIS and self-report scales was surprising, given the conceptual overlap and also given the findings of some previous studies (Anderson, Crowley et al, 2016;Anderson, McClintock et al, 2016). This picture of little association between FIS and self-report scales was surprising, given the conceptual overlap and also given the findings of some previous studies (Anderson, Crowley et al, 2016;Anderson, McClintock et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…In a first study, Anderson, Ogles, Patterson, Lambert, and Vermeersch (2009) developed a set of brief video clips of difficult situations with clients and asked 25 therapists from a university counseling center to respond to each situation in a way clients might find helpful. Anderson, Crowley, Himawan, Holmberg, and Uhlin (2016) experimentally manipulated therapist FIS by screening high and low FIS therapists (graduate students in either clinical psychology or in nonpsychological areas) using the FIS performance test and self-assessed social skills. The mean of these ratings was referred to as therapist facilitative interpersonal skills (FIS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we explored alliance, session depth, technique usage, and patient reports of feeling that the therapy overall was helpful. Expanding on previous research that has identified therapists' interpersonal skills as a strong predictor of patient outcome (e.g., Anderson, Crowley, Himawan, Holmberg, & Uhlin, 2016;Anderson et al, 2009), we found that as trainee FS increased, patients' perception of the helpfulness of the therapy as a whole significantly and robustly declined. Moreover, patient ratings of all facets of the alliance and session depth significantly decreased with moderate effects while amount of technique usage did not vary.…”
Section: Discussionmentioning
confidence: 99%